Genetic Diversity and Reassortment of Hantaan Virus Tripartite RNA Genomes in Nature, the Republic of Korea. - Jeong-Ah Kim; Won-Keun Kim; Jin Sun No; Seung-Ho Lee; Sook-Young Lee; Ji Hye Kim; Jeong Hoon Kho; Daesang Lee; Dong Hyun Song; Se Hun Gu; Seong Tae Jeong; Man-Seong Park; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:Hantaan virus (HTNV), a negative sense tripartite RNA virus of the Family Bunyaviridae, is the most prevalent hantavirus in the Republic of Korea (ROK). It is the causative agent of Hemorrhagic Fever with Renal Syndrome (HFRS) in humans and maintained in the striped field mouse, Apodemus agrarius, the primary zoonotic host. Clinical HFRS cases have been reported commonly in HFRS-endemic areas of Gyeonggi province. Recently, the death of a member of the ROK military from Gangwon province due to HFRS prompted an investigation of the epidemiology and distribution of hantaviruses in Gangwon and Gyeonggi provinces that border the demilitarized zone separating North and South Korea. METHODOLOGY AND PRINCIPAL FINDINGS:To elucidate the geographic distribution and molecular diversity of HTNV, whole genome sequences of HTNV Large (L), Medium (M), and Small (S) segments were acquired from lung tissues of A. agrarius captured from 2003-2014. Consistent with the clinical incidence of HFRS established by the Korea Centers for Disease Control & Prevention (KCDC), the prevalence of HTNV in naturally infected mice in Gangwon province was lower than for Gyeonggi province. Whole genomic sequences of 34 HTNV strains were identified and a phylogenetic analysis showed geographic diversity of the virus in the limited areas. Reassortment analysis first suggested an occurrence of genetic exchange of HTNV genomes in nature, ROK. CONCLUSION/SIGNIFICANCE:This study is the first report to demonstrate the molecular prevalence of HTNV in Gangwon province. Whole genome sequencing of HTNV showed well-supported geographic lineages and the molecular diversity in the northern region of ROK due to a natural reassortment of HTNV genomes. These observations contribute to a better understanding of the genetic diversity and molecular evolution of hantaviruses. Also, the full-length of HTNV tripartite genomes will provide a database for phylogeographic analysis of spatial and temporal outbreaks of hantavirus infection.